Language and Society in Sesenggak Sasak: A Study of the Sapir-Whorf Hypothesis - Randa Anggarista; Idham Idham; Selamet Riadi; Farizan Fahmi; Farida Jaeka (CV. Rustam, 2025)
The Sapir-Whorf hypothesis in linguistic relativity explains that the linguistic structure of a society reflects the thoughts and way speakers view their world. The Sasak people as one of the indigenous ethnic groups on Lombok Island, West Nusa Tenggara, also have a diversity of linguistic structures that reflect their outlook on life and cultural structures, one of which is in the form of sesenggak. Therefore, this study aims to identify the outlook on life of the Sasak people reflected in the linguistic construction of sesenggak based on the Sapir-Whorf hypothesis through linguistic relativity. The data in this study are in the form of texts (linguistic units) contained in sesenggak (Sasak proverbs), while the data sources in this study use primary data sources, namely sesenggak (Sasak proverbs) obtained from the book Peribahasa, Ungkapan dan Istilah Sasak by H. Lalu Muhammad Azhar, published by Yayasan Pendidikan Pariwisata Pejanggiq in 2003, as well as Sasak community leaders in Lombok. The primary data collection technique in this study was carried out using the reading and note-taking technique for written data sources, as well as the recording, listening, reading, and note-taking technique for oral data sources. To test the reliability of the data, the researcher used source triangulation, namely, combining primary data sources with secondary data to strengthen the interpretation of various findings. The data analysis technique was carried out in several stages, starting from identification, classification, interpretation, and concluding. The results of the study indicate that the linguistic structure of sesenggak reflects the cultural structure of the Sasak people, starting from their views on metaphysics, ethics, aesthetics, and logic.